Postmodernism Epistemology and Nigeria’s Educational System (2025)
Postmodernism in the educational System is to provide an enabling environment where learners will be able to unfold their freedom. It is charged with considerable level of liberalism which makes it a suitable and fertile soil far critical thinking, pluralism, democracy and creativity in education. Educational dream of the contemporary world emphasises broad-based curriculum which allows various ways of apprehending reality. The impression given by some sections of Nigeria’s National Policy on education is that Nigeria’s philosophy of education is progressive in character. However, a keen observation revealed that the National Policy on Education evidently contains some elements of essentialism. The study concludes that the role of educational philosophy is not only to connect the socio-political ideology of any given society with aims and objectives of such a society, but to constantly ensure that such a philosophy must readily reflects the reality of ever changing nature of every human society. The study recommended that the National Policy on Education be revised in the light of postmodernism as a philosophy of education, since it possesses a considerable strength to accommodate higher degree of liberal and progressive education.